Degarelix, a novel GnRH antagonist, causes minimal histamine release compared with cetrorelix, abarelix and ganirelix in an ex vivo model of human skin samples - Koechling, Wolfgang; Hjortkjaer, Rolf; Tankó, László B. (British journal of clinical pharmacology, 2010)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT? • Systemic anaphylactic reactions have been described as rare but serious adverse effects of GnRH antagonists. • The chemical development of degarelix has devoted much attention to the elimination of this risk. • Side‐by‐side comparison of the histamine releasing capacity of marketed GnRH antagonists in fresh human skin samples has not been reported yet. WHAT THIS STUDY ADDS • Our findings indicate considerable differences in the relative propensity of marketed GnRH antagonists to release histamine from cutaneous mast cells. • These findings are similar but not identical to those obtained with the conventional rat peritoneal mast cell approach. • With some further refinements the experimental set‐up using human skin samples could become a useful and low‐risk supplement to exploratory safety studies in clinical pharmacology. AIMS Early studies on gonadotrophin‐releasing hormone (GnRH) antagonists pointed out histamine‐mediated anaphylactic reactions as a potential adverse effect of these drug candidates. In this study we have compared the histamine‐releasing potential of four approved and marketed antagonists, degarelix, cetrorelix, abarelix and ganirelix in an ex vivo model of human skin samples. METHODS Human skin samples were obtained during cosmetic plastic surgery and kept in oxygenated saline solution. The samples were incubated either without or at different concentrations of the antagonists (3, 30 or 300 µg ml−1 for all, except for ganirelix 1, 10 or 100 µg ml−1). The drug‐induced effect was expressed as the increase relative to basal release. The histamine‐releasing capacity of the skin was verified by a universal histamine releaser, compound 40/80. RESULTS Degarelix had no significant effect on basal histamine release in the 3 to 300 µg ml−1 concentration range. The effect of ganirelix was moderate causing a nonsignificant increase of 81 ± 27% at the 100 µg ml−1 concentration. At 30 and 300 µg ml−1 concentrations abarelix (143 ± 29% and 362 ± 58%, respectively, P < 0.05) and cetrorelix (228 ± 111% and 279 ± 46%, respectively, P < 0.05) caused significantly increased histamine release. CONCLUSIONS In this ex vivo human skin model, degarelix displayed the lowest capacity to release histamine followed by ganirelix, abarelix and cetrorelix. These findings may provide indirect hints as to the relative likelihood of systemic anaphylactic reactions in clinical settings.